2021
DOI: 10.1111/jcpt.13447
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status determines the impact of metformin on circulating prolactin levels in premenopausal women

Abstract: The pituitary, located outside the blood-brain barrier, 1 accumulates larger amounts of metformin than other rat brain structures 2 and is probably an important target for metformin action. The drug was found to normalize secretory function of overactive thyrotropes, 3,4 gonadotropes 5,6 and lactotropes. [7][8][9] Its prolactin-lowering effect was observed in patients with prolactin-secreting tumours, 7 iatrogenic hyperprolactinaemia, 8 traumatic brain injury, 7 empty sella syndrome 7 and polycystic ovary synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…To reduce gonadotropin levels, patients have to receive high doses of metformin, commonly used in type 2 diabetes but higher than recommended to prediabetic women [40]. However, chronic treatment with 2.55-3 g metformin daily was well tolerated by the participants of the current study, and there were no cases of serious adverse effects associated with high-dose metformin treatment in our previous studies [26,27]. Moreover, a network meta-analysis showed that 6-month treatment of overweight and obese subjects without diabetes with 3 g metformin daily was well tolerated and superior to treatment with lower doses in reducing body weight and improving glucose homeostasis [28].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…To reduce gonadotropin levels, patients have to receive high doses of metformin, commonly used in type 2 diabetes but higher than recommended to prediabetic women [40]. However, chronic treatment with 2.55-3 g metformin daily was well tolerated by the participants of the current study, and there were no cases of serious adverse effects associated with high-dose metformin treatment in our previous studies [26,27]. Moreover, a network meta-analysis showed that 6-month treatment of overweight and obese subjects without diabetes with 3 g metformin daily was well tolerated and superior to treatment with lower doses in reducing body weight and improving glucose homeostasis [28].…”
Section: Discussionmentioning
confidence: 65%
“…This finding suggests that even mild disturbances in vitamin D homeostasis may impair the impact of metformin on overactive gonadotropes. Considering the correlations between 25-hydroxyvitamin D levels and treatment-induced changes in gonadotropins and prolactin [26], it may be assumed that a deteriorating effect of hypovitaminosis D on the pituitary effects of metformin increases with its severity, which may be of importance in cases of patients with extremely high gonadotropin levels. Importantly, the impact of metformin on FSH and LH levels seems to be determined by actual vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it also correlated with the improvement in insulin sensitivity. Since the vitamin D status was not neutral to the glucose and insulin response to metformin [ 233 ], it is not possible to say whether the vitamin D-dependent action of metformin on the lactotroph function was direct or indirect, mediated by the improvement in insulin sensitivity.…”
Section: Metformin Actions On Pituitary Tumor Cells and Gastroenteropancreatic Neuroendocrine Tumor Cellsmentioning
confidence: 99%
“…However, prolactin and vitamin D interactions are poorly understood. Metformin has been found to reduce prolactin levels only if 25-hydroxyvitamin D levels were within the reference range, and this effect correlated with 25-hydroxyvitamin D levels [ 30 ]. However, metformin’s inhibitory effect on lactotrope secretory function was clearly inferior to that of dopaminergic agents, and the study focused on metformin’s prolactin-lowering properties [ 31 ].…”
Section: Introductionmentioning
confidence: 99%